Designing for cycle traffic. International principles and practice. - (:unkn) unknown (ICE Institution of Civil Engineers Publishing, 2018)
Designing for Cycle Traffic compares and evaluates international principles and practices for designing for cycle traffic. It sets design for cycling in the wider context of public realm design, traffic planning, traffic engineering and traffic management. The book shows how effective design can create efficient transport systems that support economic vibrancy, social activity, and environmental sustainability. A key theme is that only distinct and separate provision for cycle traffic can ensure the creation of attractive and comfortable infrastructure for cyclists.
Keywords: Individualverkehr; Fahrradverkehr; Infrastruktur; Fahrradinfrastruktur; Mobilität; Verkehrsplanung; Kreisverkehr; Knotenpunkt; Lichtsignalanlage; Radverkehrsplanung; Fahrradparken